Functional validation of novel levamisole resistance marker S168T in Haemonchus contortus - Alistair Antonopoulos; Claude L. Charvet; Kirsty Maitland; Stephen R. Doyle; Cédric Neveu; Roz Laing (International Journal for Parasitology: Drugs and Drug Resistance, 2024)
Recently, a S168T variant in the acetylcholine receptor subunit ACR-8 was associated with levamisole resistance in the parasitic helminth Haemonchus contortus. Here, we used the Xenopus laevis oocyte expression system and two-electrode voltage-clamp electrophysiology to measure the functional impact of this S168T variant on the H. contortus levamisole-sensitive acetylcholine receptor, L-AChR-1.1. Expression of the ACR-8 S168T variant significantly reduced the current amplitude elicited by levamisole compared to acetylcholine, with levamisole changing from a full to partial agonist on the recombinant L-AChR. Functional validation of the S168T mutation on modulating levamisole activity at the receptor level highlights its critical importance as both a mechanism and a marker of levamisole resistance.